Consultations and referrals for dyspepsia in general practice—a one year database survey. Issue 910 (1st August 2001) - van Bommel, M J J; Numans, M E; de Wit, N J; Stalman, W A B
Abstract : OBJECTIVE: Dyspepsia usually presents first in primary care. There are many reasons for referral including urgent problems (for example, haematemesis and melaena), treatment failure, or to exclude serious pathology. Referral will change the population characteristics of primary and secondary care dyspeptics. Many of the guidelines for primary care dyspepsia, however, are based on secondary care research on these referred patients. The aim of this study was to describe the prevalence of dyspepsia in general practice, the characteristics of patients presenting with dyspepsia in primary care, and the clinical and non-clinical determinants of referral in these patients. DESIGN: Cross sectional survey of the consultation records of patients presenting with dyspepsia in primary care during a one year period. METHODS: Dyspeptic patients who consulted their general practitioner (GP) in 1997 were selected on the basis of International Classification of Primary Care codes using a computer search among 20 sentinel practices affiliated with the Utrecht Network of General Practitioners. Cross tables and logistic regression analysis were carried out to reveal patient characteristics and determinants of referral. RESULTS: The prevalence of dyspepsia presenting in primary care in 1997 was 3.4% (1740/48958). These patients were usually not referred during the first consultation. Men, elderly patients, and patients with a previous history of dyspepsia were referred to secondary care more frequently than other dyspeptic patients. Patients diagnosed with both irritable bowel syndrome and dyspepsia were at risk of being referred most. CONCLUSION: Dyspepsia is a frequently occurring complaint in primary care and patients are usually treated by their GP. Besides clinically relevant reasons for referral, dyspeptic patients with irritable bowel syndrome seem to be more "at risk" of being referred to secondary care than other dyspeptic patients. The differences between primary and secondary care dyspeptic patients should be taken into account when interpreting research for guideline purposes. Further research is needed to clarify the background of the relation between irritable bowel syndrome and dyspepsia and its influence on referral.